The Relationship Between Medication Adherence and Quality of Life in Renal Transplant Patients - M. Shabany-Hamedan; J. Mohmmad-Aliha; R. Shekarabi; AF. Hosseini (Iran University of Medical Sciences, 2010)
Background and Aim: Post-kidney transplant survival relies on patient adherence to the intake of immunosuppressive medication. Non-adherence to immunosuppressive drugs leads to rejection, graft loss, dialysis, lower quality of life, increased costs and mortality. Quality of life may be useful to identify non-adherence. The aim of the current study was to examine the relationship between medication adherence and quality of life in renal transplant patients.   Materials and Method: This was a descriptive cross-sectional study in which 230 patients who were more than 18 years old and at least 3 month elapsed from their graft participated. Data were collected by Immunosuppressant Therapy Adherence Scale (2005) and Quality of Life in Kidney Transplant Patient questionnaires. Data were analyzed by SPSS, version 15.   Results: Finding showed that the mean score and standard deviation of quality of life were 21.65 and 4.039, respectively, and 57.8% of patients were non-adherent. A statistically significant and indirect relationship was found between adherence and quality of life (p < 0.001, rETA=0.23). Conclusion: Regarding the results that showed the relationship between adherence and quality of life in patients, nurses should consider immunosuppressant adherence in teaching and caring as a health promoting strategy.